Pengaruh Aspek Kognitif Terhadap Prestasi Akademik Mahasiswa - Ulandari, Efy; Efendi, Achmad; Damingun (Sekretariat Pusat Lembaga Komunitas Informasi Teknologi Aceh, 2025)
This study aims to examine the influence of cognitive aspects on students' academic achievement. Cognitive aspects include the ability to think, understand, remember, analyze, and apply knowledge in the learning process. The research employs a quantitative approach, with a population consisting of 328 eighth-semester students from the Management undergraduate program at Universitas Muhammadiyah Kalimantan Timur. A sample of 180 respondents was selected using random sampling based on the Slovin formula. Data were collected through questionnaires and academic records (GPA). The data were analyzed using simple linear regression with the assistance of SPSS version 25. The results indicate that cognitive aspects have a positive and significant effect on students' academic achievement. These findings highlight the importance of developing cognitive abilities to support academic success in higher education.